Study of the compound water cyclone's concentrating efficiency of free gold from placer material - Daniel E. Walsh; P. D. Rao (Canadian Institute of Mining, Metallurgy and Petroleum, 1988)
"A four-inch compound water cyclone (CWC) was tested to evaluate its gold recovery characteristics when processing -4.8 mm run-or-pit, placer material. Neutron activated placer gold particles (840 to 37 microns) were used as radiotracers (/98Au) in a closed circuit ewe test loop to determine concentrator recovery; a procedure believed unique to this study. The effect on gold recovery of gold size and shape, feed pulp density, feed pressure, vortex finder clearance (VFC), ewe cone type, top-size of the feed solids, presence or absence of heavy minerals in the feed, and the quantity of-37 micron slimes in the feed was investigated in over 300 tests.CWC concentration ratio and the top-size of the underflow solids were both affected by cone type, VFC, and feed pressure. Gold recovery was significantly affected by gold size, gold shape, and concentration ratio. These effects are complex, because significant size-concentration ratio and size-shape interactions exist. Radiotracer techniques showed gold particles had a residence time within the ewe of approximately one second. This study suggests ewe gold recovery is a concentration. This work suggests ewe gold recovery is a function of particle size and shape, and the flow rate through the cyclone. CWC cone ""bed density"" is considered important only as a thin, protective layer, which shields coarser gold particles from the entraining currents and facilitates their movement through the CWC.IntroductionCompound water cyclones (CWC), or automedium cyclones, are enhanced gravity concentrators for the beneficiation for slurries of sand, coal, and ground ore (Fig. 1). They are called compound water cyclones because of the compound slopes of their basal cones (Fig. 2) and are operated to suppress classification phenomena in favour of gravity concentration effects. The compound water cyclone is not a new wet concentrator. It was developed in the late 1950s by Dr. Jan Visman through research sponsored by Canada's Department of Energy, Mines, and Resources. Since that time, it has become a common unit in coal washeries for cleaning fine coal. CWCs and other versions of concentrating cyclones have also shown promise for heavy minerals and precious metals recovery."